Use of the subacromial balloon in irreparable massive rotator cuff tears - Berrocal-Sánchez, Carlos (2023)
The rotator cuff injury is a significant cause of shoulder pain and dysfunction. Treating massive and irreparable rotator cuff tears remains a major challenge for orthopedists due to their complexity and severity. One promising alternative for managing these cases is the use of subacromial balloons. In this study, we present the case of a 67-year-old woman diagnosed with a massive and irreparable rotator cuff tear in her right shoulder (Grade III Patte, Grade IV Goutallier, and Grade II Hamada), without glenohumeral arthritis, intact biceps tenosynovitis, and subscapularis. The preoperative Constant score was 40 points. The patient underwent partial arthroscopic repair of the supraspinatus and infraspinatus tendons, along with a suprapectoral biceps tenodesis and subacromial balloon placement. Postoperative rehabilitation led to improved range of motion, reduced pain, and increased strength in the right shoulder. The postoperative Constant score reached 80 points at the twelve-week mark. The subacromial balloon proves to be a promising treatment alternative for irreparable rotator cuff injuries, providing optimal short-term results in terms of pain relief and functionality.